PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM DAN DANA ALOKASI KHUSUS TERHADAP BELANJA DAERAH PEMERINTAH KABUPATAN/KOTA PROVINSI KALIMANTAN BARAT - Finalianti Roskaputri; Haryono; Elok Heniwati (Berajah Journal, 2024)
This study aims to test and identify the effect of Regional Original Revenue, General Allocation Fund and Special Alloation Fund on Regional Expenditure in order to determine the contribution of factors that affect regional expenditure such as the three types of funds. The data for this study were obtained by the Regional Finance and Assets Agency of West Kalimantan Province and supporting data from the website of the Directorate General of Fiscal Balance covering 14 districts/cities in West Kalimantan Province in 2018-2022. Using Eviews 12, this research uses panel data regression as an analysis technique. Panel data regression shows that the Common Effect Model is the best model found in this study. The research findings show that there is an influence of Regional Original Revenue and Special Allocation Fund on Regional Expenditure. Meanwhile, simultaneously, Regional Expenditure in all districts/cities of West Kalimantan Province is positively and significantly influenced by Local Own Revenue, General Allocation Fund and Special Allocation Fund.